Development and Validation of Confocal Endomicroscopy Diagnostic Criteria for Low-Grade Dysplasia in Barrett's Esophagus. Issue 4 (April 2019) - di Pietro, Massimiliano; Bertani, Helga; O'Donovan, Maria; Santos, Patricia; Alastal, Hani; Phillips, Richard; Ortiz-Fernández-Sordo, Jacobo; Iacucci, Marietta; Modolell, Ines; Reggiani Bonetti, Luca; Ragunath, Krish; Wernisch, Lorenz
Abstract : OBJECTIVES: Low-grade dysplasia (LGD) in Barrett's esophagus (BE) is generally inconspicuous on conventional and magnified endoscopy. Probe-based confocal laser endomicroscopy (pCLE) provides insight into gastro-intestinal mucosa at cellular resolution. We aimed to identify endomicroscopic features and develop pCLE diagnostic criteria for BE-related LGD. METHODS: This was a retrospective study on pCLE videos generated in 2 prospective studies. In phase I, 2 investigators assessed 30 videos to identify LGD endomicroscopic features, which were then validated in an independent video set (n = 25). Criteria with average accuracy >80% and interobserver agreement κ > 0.4 were taken forward. In phase II, 6 endoscopists evaluated the criteria in an independent video set (n = 57). The area under receiver operating characteristic curve was constructed to find the best cutoff. Sensitivity, specificity, interobserver, and intraobserver agreements were calculated. RESULTS: In phase I, 6 out of 8 criteria achieved the agreement and accuracy thresholds (i) dark nonround glands, (ii) irregular gland shape, (iii) lack of goblet cells, (iv) sharp cutoff of darkness, (v) variable cell size, and (vi) cellular stratification. The best cutoff for LGD diagnosis was 3 out of 6 positive criteria. In phase II, the diagnostic criteria had a sensitivity and specificity for LGD of 81.9% and 74.6%, respectively, with an area under receiver operating characteristic of 0.888. The interobserver agreement was substantial (κ = 0.654), and the mean intraobserver agreement was moderate (κ = 0.590). CONCLUSIONS: We have generated and validated pCLE criteria for LGD in BE. Using these criteria, pCLE diagnosis of LGD is reproducible and has a substantial interobserver agreement.